Impact of Covid 19 Pandemic on Dentists: Psychological Evaluation using DASS 21 - Vineet Golchha; Pooja Sharma; Bhuvan Deep Gupta; Nancy Yadav (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The outbreak of coronavirus disease 2019 (COVID-19) in the area of Wuhan, China, hasevolved rapidly into a public health crisis. Despite having high standards of knowledge and practices, dentalpractitioners around the globe are in a state of anxiety or fear. Being on the list of high-risk professions,dentists are very much expected to develop stress due to the current pandemic situation indicating a need toevaluate the effect of COVID 19 on the psychological status of Indian dentists.Methodology: The data was collected through well-structured Google form from 500 dentists workingin Delhi NCR. The entire form had two components. The first part of the form collected the informationregarding the demographic profile of the dentists whereas the second part of questionnaire consisted ofpsychological evaluation using well established psychological scale DASS 21.Result: The results showed that 8% of Indian dentist showed signs of severe depression and 17% hadmoderate signs. 9% showed moderate and 13% showed mild anxiety. 8% showed severe stress and 24%had moderate signs of stress. Significant correlation was found between depression and anxiety with stress.Conclusion: Dentists are undergoing stress which in turn can have adverse effects on their physical andmental well-being in a long run. There is a need to evolve with the current COVID 19 pandemic andbrainstorming the ways to encourage the safer practice and decrease the levels of depression, anxiety andstress among dentist.